2019
DOI: 10.1002/lol2.10106
|View full text |Cite
|
Sign up to set email alerts
|

Copepod respiration increases by 7% per °C increase in temperature: A meta‐analysis

Abstract: Exponential increase in respiration rate with increasing temperature in poikilotherms is well documented, however, the rate of change varies greatly across copepod taxa. Studies often report magnitude of change, but the rate of change in respiration across multiple temperatures is equivocal. We used 32 studies spanning 78 yrs of research and 50 copepod species (three orders) to quantify percent change in respiration rates per one‐unit change in temperature. We found that copepod respiration rates increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…Q 10 was used as the effect size. Variance in Q 10 was calculated using the delta method (Hoef, ) when sample sizes and variances in metabolic rates were provided by original authors (using a similar method as Heine et al, ; see File S2: https://doi.org/10.6084/m9.figshare.10125248.v2). Studies where variances in Q 10 s could not be calculated were excluded from meta‐analyses but included when graphing results.…”
Section: Methodsmentioning
confidence: 99%
“…Q 10 was used as the effect size. Variance in Q 10 was calculated using the delta method (Hoef, ) when sample sizes and variances in metabolic rates were provided by original authors (using a similar method as Heine et al, ; see File S2: https://doi.org/10.6084/m9.figshare.10125248.v2). Studies where variances in Q 10 s could not be calculated were excluded from meta‐analyses but included when graphing results.…”
Section: Methodsmentioning
confidence: 99%
“…While an inverse relationship between the metabolic rate and temperature is well documented in insects across all gas patterns (see [66] and references therein), our results show that metabolic rate exhibits an 8.13% per • C increase in temperature, at least for insects breathing discontinuously. Although not directly related, another meta-analytic study found that copepods respiration increases by 7% per • C increase in temperature [29]. Thus, we suggest that this range reflects the general characteristics of arthropod ectothermic poikilotherms.…”
Section: Discussionmentioning
confidence: 56%
“…The comparison of studies using slope is advantageous over common Q 10 values in two ways. It can be used to compare metabolic rate across more than two temperatures and its interpretation does not require reference to other Q 10 values [29]. Irlich et al [61] conducted a meta-analytic evaluation of metabolic-rate temperature relationships on a global level (i.e., irrespective of the gas pattern) in insects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations